Answer:
Step-by-step explanation:The problem is very hard to read. When using exponents, please add the "^" in front. For example, is 132 actually 132, or is it 13^2? The right triangle is not shown, so we really don't know which is the hypotenuse. Also be carefull with spacing. Making some assumptions, here is how the answer might look:
Both have the correct formula: a^2 + b^2 = c^2, assuming c is the hypotenuse.
If c is the hypotenuse, then the expression should be:
7^2 + b^2 = 13^2, or
49 + b^2 = 169
I like Sheridan's answer. So let's continue:
49 + b^2 = 169
b^2 = 169-49
b^2 = 120
b = 10.954 . . .
Yep, I'm on Sheridan's side. [That is, unless 72 is 72 and not 7^2, etc.]